2019
DOI: 10.3390/cells8020155
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Pathway Proteins in Normal and Malignant Hematopoiesis

Abstract: The regulation of oxygen (O2) levels is crucial in embryogenesis and adult life, as O2 controls a multitude of key cellular functions. Low oxygen levels (hypoxia) are relevant for tissue physiology as they are integral to adequate metabolism regulation and cell fate. Hence, the hypoxia response is of utmost importance for cell, organ and organism function and is dependent on the hypoxia-inducible factor (HIF) pathway. HIF pathway activity is strictly regulated by the family of oxygen-sensitive HIF prolyl hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 82 publications
1
34
0
Order By: Relevance
“…In support of such a model, we found that activation of Nrf2-and Hif-driven gene programs are maintained in EPCR + /CD34 − SLAM cells. Notably, Nrf2 and Hif pathways are also required for HSC quiescence, and their deletion leads to HSC mobilization from the BM [43,53]. Thus, further studies can assess the degree to which EPCR cooperates and/or converges with metabolic control mechanisms like Nrf2 and Hif to enforce quiescence and localization of EPCR + HSCs in the BM niche, particularly under inflammatory stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In support of such a model, we found that activation of Nrf2-and Hif-driven gene programs are maintained in EPCR + /CD34 − SLAM cells. Notably, Nrf2 and Hif pathways are also required for HSC quiescence, and their deletion leads to HSC mobilization from the BM [43,53]. Thus, further studies can assess the degree to which EPCR cooperates and/or converges with metabolic control mechanisms like Nrf2 and Hif to enforce quiescence and localization of EPCR + HSCs in the BM niche, particularly under inflammatory stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia and a low ROS level are required for HSCs self-renewal and maintenance. [1][2][3][4] Optimization of the levels of environmental factors such as oxygen, cytokines, and fatty acids enables maintenance of HSCs quiescence ex vivo. 5 Small molecules that can maintain low ROS levels 6 and inhibit cell apoptosis or autophagy 7 are also useful for maintenance or expansion of HSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Besides intrinsic transcriptional regulation, the birth of hematopoietic stem cells (HSCs) is regulated by multiple exogenous factors, such as hypoxic and extracellular components. Hypoxia and a low ROS level are required for HSCs self‐renewal and maintenance 1–4 . Optimization of the levels of environmental factors such as oxygen, cytokines, and fatty acids enables maintenance of HSCs quiescence ex vivo 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Another important characteristic of the niches is the distribution of oxygen in the BM microenvironment. The oxygen concentration controls essential cellular processes for the maintenance of the physiological behavior of tissues and organs and is considered a key parameter in the regulation of the survival and quiescence of HSCs in the BM niches [ 15 ]. The oxygen concentration is not distributed evenly in the microenvironment of the niches: it is lower in the endosteal niche and gradually increases towards the perivascular niche [ 16 ] because of proximity of blood vessels that provide oxygen supply.…”
Section: Introductionmentioning
confidence: 99%